Heme Oxygenase-1 protects astroglia against manganese-induced oxidative injury by regulating mitochondrial quality control. (1st October 2018) - Gorojod, Roxana Mayra; Alaimo, Agustina; Porte Alcon, Soledad; Martinez, Jimena Hebe; Cortina, María Eugenia; Vazquez, Elba Susana; Kotler, Mónica Lidia
Highlights: Manganese (Mn) exposure induces HO-1 upregulation in rat astrocytoma C6 cells. HO-1 decreases both intracellular and mitochondrial reactive oxygen species. Hemin-induced HO-1 ameliorates Mn- induced mitochondrial damage. HO-1 maintains both mitochondrial fusion/fission and biogenesis/mitophagy balances. Abstract: Heme Oxygenase-1 (HO-1), a stress- responsive enzyme which catalyzes heme degradation into iron, carbon monoxide, and biliverdin, exerts a neuroprotective role involving many different signaling pathways. In Parkinson disease patients, elevated HO-1 expression levels in astrocytes are involved in antioxidant defense. In the present work, employing an in vitro model of Mn 2+ -induced Parkinsonism in astroglial C6 cells, we investigated the role of HO-1 in both apoptosis and mitochondrial quality control (MQC). HO-1 exerted a protective effect against Mn 2+ injury. In fact, HO-1 decreased both intracellular and mitochondrial reactive oxygen species as well as the appearance of apoptotic features. Considering that Mn 2+ induces mitochondrial damage and a defective MQC has been implicated in neurodegenerative diseases, we hypothesized that HO-1 could mediate cytoprotection by regulating the MQC processes. Results obtained provide the first evidence that the beneficial effects of HO-1 in astroglial cells are mediated by the maintenance of both mitochondrial fusion/fission and biogenesis/mitophagy balances. Altogether, our data demonstrate a pro-survival function for HO-1 in Mn 2+ -induced apoptosis that involves the preservation of a proper MQC. These findings point to HO-1 as a new therapeutic target linked to mitochondrial pathophysiology in Manganism and probably Parkinson´s disease.